2019
DOI: 10.7759/cureus.5541
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Drug Resistance in Previously-Treated Pulmonary Tuberculosis Patients Registered at a Chest Clinic in South Delhi, India

Abstract: Introduction Drug-resistant tuberculosis (DR-TB) is a major concern to effective control of tuberculosis (TB) in India and the likelihood of drug resistance increases with repeated exposure to anti-TB drugs. India has emerged as one of the leading contributors of DR-TB in the world posing a major threat to TB control. In the current study, we aim to find the burden and factors associated with drug resistance in previously treated pulmonary TB patients. Methods A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
1
2
Order By: Relevance
“…Additionally, the production of drug-resistant strains, low patient immunity, and comorbidities such as diabetes or other pulmonary infections are also factors that cannot be ignored ( Shivekar et al, 2020 ; Antonio-Arques et al, 2021 ; Antimicrobial Resistance Collaborators, 2022 ; Williams et al, 2022 ). However, this study did not find an association between BMI and binding resistance, while previous studies have shown that higher BMI was negatively associated with being a relapse/defaulter/treatment-failure cases ( Goswami et al, 2014 ; Sharma et al, 2019 ). Improved nutritional status, which can positively influence immunity and treatment outcome, could be cited as a possible explanation; but their findings could also have been an artifact of reverse causation, as implicated by deterioration of general health among relapse/defaulter/treatment-failure cases.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the production of drug-resistant strains, low patient immunity, and comorbidities such as diabetes or other pulmonary infections are also factors that cannot be ignored ( Shivekar et al, 2020 ; Antonio-Arques et al, 2021 ; Antimicrobial Resistance Collaborators, 2022 ; Williams et al, 2022 ). However, this study did not find an association between BMI and binding resistance, while previous studies have shown that higher BMI was negatively associated with being a relapse/defaulter/treatment-failure cases ( Goswami et al, 2014 ; Sharma et al, 2019 ). Improved nutritional status, which can positively influence immunity and treatment outcome, could be cited as a possible explanation; but their findings could also have been an artifact of reverse causation, as implicated by deterioration of general health among relapse/defaulter/treatment-failure cases.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our study, patients who received more than two previous anti-TB treatments (ATT) (compared to one) had a 2.4 times higher risk of DR-TB in India and 3.25 times increased odds of confirmed MDR-TB in Mali [31,32], while a study from Ethiopia found an association between two or more previous TB treatments and any type of drug resistance [30]. In Bangladesh, 54% of the 293 TB patients who had received TB treatment more than once were MDR-TB, and 97% MDR-TB patients in the Philippines reported a previously failed Category 2 treatment, indicating they were treated at least twice for TB in the past [33,34].…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the production of drug-resistant strains, low patient immunity, and comorbidities such as diabetes or other pulmonary infections are also factors that cannot be ignored (Shivekar et al, 2020;Antonio-Arques et al, 2021;Antimicrobial Resistance Collaborators, 2022;Williams et al, 2022). However, this study did not find an association between BMI and binding resistance, while previous studies have shown that higher BMI was negatively associated with being a relapse/defaulter/treatment-failure cases (Goswami et al, 2014;Sharma et al, 2019). Improved nutritional status, which can positively influence immunity and treatment outcome, could be cited as a possible explanation; but their findings could also have been an artifact of reverse causation, as implicated by deterioration of general health among relapse/defaulter/treatment-failure cases.…”
Section: Discussioncontrasting
confidence: 52%